Reaction Of Capital Market To The Emergence Of Covid-19 In Indonesia Stock Index LQ-45 - Devy Murdani; Muh. Salahuddin; Naili Rahmawati (UIN Mataram, 2021)
This research was conducted to see the analysis of the capital market reaction to the pandemic of COVID-19 in Indonesia, whether there is the difference in Abnormal Return and Trade Volume Activity before and after the COVID-19 first case in Indonesia on March 2, 2020 by using 38 sample of 45 stocks in Index LQ-45 which listed from the period of February to July 2020. This research type is quantitative with research method use were Paired Sample t-Test and Wilcoxon Signed Rank test. The results of this research indicated that there is no significant difference in Abnormal Return (AR) and Trade Volume Activity (TVA) before and after the emergence of Corona Virus (COVID-19) in Indonesia of stock index Lq45.